Leucocytes in adult burrowing parrots Cyanoliseus patagonus in the wild: variation between contrasting breeding seasons, gender, and individual condition - Plischke, Andreas; Quillfeldt, Petra; Lubjuhn, Thomas; Merino, Santiago; Masello, Juan F.; Justus Liebig University Giessen (My University, 2010)
Wild birds exposed to stressors may modulate their investment in immunity. We studied the leucocytes of breeding burrowing parrots (Cyanoliseus patagonus) in Patagonia during five breeding seasons, during which global climate events such as a strong La Niña and a weak El Niño occurred. We observed strong inter-annual variation in the ratio of heterophils to lymphocytes (H/L), with higher H/L during the adverse conditions of La Niña compared with the favourable conditions of El Niño for the studied region. Nevertheless, highest H/L were found in the breeding season following a La Niña event; this is probably explained by a combination of long-term detrimental effects of climatic conditions and other, e.g. biotic, stressors. Males had higher H/L than females, and H/L ratios were negatively related to individual body condition.
Keywords: Body condition; Blood cell counts; Climatic conditions; El Niño southern oscillation (ENSO); H/L ratio; Psittaciformes; Sex differences; ddc:570; ddc:590